Windows into the soul: surveillance and society in an age of high technology - Marx, Gary T. (The University of Chicago Press, 2016)
Frontmatter -- Contents -- Preface -- Acknowledgments -- Introduction -- 1 Defining the Terms of Surveillance Studies -- 2 So What's New? Classifying Means for Change and Continuity -- 3 So What's Old? Classifying Goals for Continuity and Change -- 4 The Stuff of Surveillance: Varieties of Personal Information -- 5 Social Processes in Surveillance -- 6 A Tack in the Shoe and Taking the Shoe Off : Resistance and Counters to Resistance -- 7 Work: The Omniscient Organization Measures Everything That Moves -- 8 Children: Slap That Baby's Bottom, Embed Th at ID Chip, and Let It Begin -- 9 The Private within the Public: Psychological Report on Tom I. Voire -- 10 A Mood Apart: What's Wrong with Tom? -- 11 Government and More: A Speech by the Hon. Rocky Bottoms to the Society for the Advancement of Professional Surveillance -- 12 Techno- Fallacies of the Information Age -- 13 An Ethics for the New (and Old) Surveillance -- 14 Windows into Hearts and Souls: Clear, Tinted, or Opaque Today? -- Appendix: A Note on Values: Neither Technophobe nor Technophile -- Notes -- References -- Index